Un-tied nations : the United Nations, peacekeeping and global governance - Seaman, Kate (Farnham, Surrey, England : Ashgate, 2014)
Using a number of relevant case studies, this book provides a concise and analytical introduction to the ongoing debates around the development of global governance, global security governance, and the continuous impact these are having on the ability of the United Nations to act as an international peacekeeper.
Contents note continued: 7.The End of Legitimate Interventions? -- The United Nations and State Creation: Beyond the Original Mandate? -- Resources and Mandates -- Military Advice.
Includes bibliographical references (pages 185-229) and index.
Keywords: United Nations -- Peacekeeping forces; United Nations -- Armed Forces; Nation-building.; Peace-building.; International cooperation